Advancing AI Literacy in Danish TVET through Craftsmanship and Socio-Material Perspectives - Haarsbjerg, Marianne; Georgsen, Marianne (Proceedings of the International Conference on Networked Learning, 2026)
The rapid development of artificial intelligence (AI), particularly generative AI, is transforming how knowledge, skills, and competences are understood and enacted in Technical and Vocational Education and Training (TVET). Such transformation raises pressing questions about how AI literacy can be meaningfully advanced within educational traditions grounded in material practice and professional identity. Drawing on socio-material theory and Richard Sennett’s notion of craftsmanship, this paper conceptualizes AI literacy as a situated, networked, and relational practice rather than a purely cognitive or technical skill. The paper introduces a framework consisting of five learning strategies: AI Independent, AI Aware, AI Supported, AI Enhanced, and AI Centric learning developed within the Danish [Blinded for review] project. These strategies illustrate how learners can progress from foundational manual mastery toward hybrid forms of digital–material craftsmanship and critical engagement with AI. In this perspective, AI is understood not simply as a tool but as an active participant in educational assemblages that connect humans, technologies, and educational settings. This paper presents part of an ongoing research project which applies a design-based research approach. As part of the research project, we are currently conducting document analysis of ministerial orders for TVET. A preliminary analysis from bricklayer education exemplifies how knowledge, skills, and competences can be mapped across the five strategies. The findings highlight that the fundamentals of craftsmanship remain essential for developing critical AI literacy in TVET. First, students must be able to act independently of AI to later evaluate, collaborate with, and shape it responsibly. Conversely, AI-centric learning opens new possibilities for innovation, design, and ethical reflection, challenging conventional boundaries between human and machine agency. By combining craftsmanship with socio-material and networked learning perspectives, the framework contributes to current debates on what it means to be skilled in an age of intelligent technologies. It provides a vocabulary for teachers and researchers to discuss progression, agency, and relationality in AI-integrated vocational education. Future research will extend the analysis of ministerial orders across vocational domains to examine how AI-related, craft-specific, and transversal competences are recognized, aligned, and developed within networked learning environments.